AKTIVITAS ANTIDIABETES EKSTRAK ETANOL DAUN Calophyllum inophyllum Linn TERHADAP KADAR GULA DARAH MENCIT (Mus musculus) MODEL DIABATES MELLITUS - Ukratalo, Abdul M; Kaihena, Martha; Ramadhany, Muhammad Reza (Pattimura University, 2022)
The use of herbal remedies in treating diabetes mellitus has been used for generations because in addition to the relatively small side effects, the price is more economical. Bintangur (Calophyllum inophyllum Linn) is a plant that has multiple benefits. Bintangur contains compounds derived from xantona, coumarins, flavonoids, benzodipiranones, triterpenoids and steroids. Flavonoid compounds in star leaves are thought to be able to capture free radicals that cause damage to cells β the pancreas that causes diabetes mellitus. The purpose of this study was to determine the potential of ethanol extract of Calophyllum inophyllum Linn leaves against decreasing blood sugar levels of diabetes mellitus mice. Mice of 20 heads divided into 5 groups KN, K (-), K (+), P1 = dose 0.2 ml / head / day and P2 = dose 0.4 ml / head / day. In the K(-), K(+), P1 and P2 groups STZ induction and blood sugar levels were observed. After an increase in blood sugar levels in the K (+) group, metformin drugs were given, P1 and P2 were given stargur leaf extract according to a predetermined dosage. Observation of post-induction blood sugar levels was observed on days 7 and 14. The research data were then analyzed using the ANOVA test. The results of the ANOVA test showed that the calculated F value was 177.503 with an F probility of 0.000 (sig<0.05) which means that the administration of stargur leaf ethanol extract had an effect on kgd mice.